POTENSI PENGEMBANGAN OBJEK WISATA RIAM DI DESA MAYAK, KABUPATEN BENGKAYANG, KALIMANTAN BARAT - Sari, Julia Purnama; Makhrian, Andy; Sugara, Ayub; Jufrise, Siska; Haikal Fikri, Muhammad (TRIBUTE: JOURNAL OF COMMUNITY SERVICES, 2023)
BENGKAYANG REGENCY IS A DISTRICT IN WEST KALIMANTAN, WHICH IS A DIVISION OF SAMBAS REGENCY. Bengkayang has a tourism sector that plays an important role in the regional economy in Mayak Village. Mayak Village has so much potential, one of which is the development of the Riam tourist attraction. The potential for cascades in Mayak Village are Riam Irang, Riam Dahan, Riam Batu Besusun and Riam Kamang. With the development of the Riam-riam tourist attraction in Mayak Village, there is great hope that the community will be involved in its management so that it can increase business opportunities and increase village income and can increase the Village Development Index (IDM).